Emergency valve surgery for infective endocarditis complicated by acute intracranial hemorrhage: A case report. (2017) - Goto, Takasumi; Ohata, Toshihiro; Shijo, Takayuki; Yoshioka, Daisuke; Kaneko, Mitsunori
Highlights: Optimal timing of surgical treatment for infective endocarditis (IE) complicated by intracranial hemorrhage remains controversial. We believe that emergency surgery in active infective endocarditis patients with intracranial hemorrhage is justified if there are multiple indications for emergency surgery and the intracranial hemorrhage is small. Further evaluation is warranted regarding the risk of subsequent hemorrhage in patients with intracranial hemorrhage who require emergency valve surgery. Abstract: Introduction: Optimal timing of surgical treatment for infective endocarditis (IE) complicated by intracranial hemorrhage remains controversial. Presentation of case: A 43-year-old man with IE received appropriate antibiotic therapy but had recurrence of cerebral infarction and intracranial hemorrhage (ICH). Emergency valve surgery was performed 2 days after ICH onset because of heart failure and recurrence of cerebral complications. Postoperatively, he showed no neurologic symptoms; neuroimaging showed no enlargement of ICH. Discussion: Postoperative risk of neurologic deterioration may be relatively lower than previously thought in patients with IE who undergo surgery within 1 month after ICH onset. Conclusions: Emergency surgery in patients with ICH is justified in cases of multiple indications for such small ICH. Further evaluation regarding the risk of subsequent hemorrhage in patients with ICH who require emergency valve surgery is warranted.